Internet, Laman Web Pornografi dan Kaedah Psikospiritual Islam dalam Menangani Keruntuhan Akhlak Remaja Pelayar Laman Web Pornografi - Abdul Aziz, Nor Azah (Jurnal Usuluddin, 2009)
This article discussed benefits of internet technology in providing massive information and communication throughout the entire world. Instead, the negative issues related to pornography site surfing which can ruin teenagers morality and suggestion from Islamic psychospiritual perspective are also discussed to suggest treatment in dealing with teenagers’ soul.